(958) Basic Economic Concepts for Health Planners المفاهيم الاقتصادية الأساسية للقائمين على التخطيط الصحى - W.A. Hassouna. (INP, 2024)
In this publication, the author presents some basic economic concepts, emphasizing the definition and illustration of certain economic and accounting concepts that are useful to those interested in public administration in general and specifically in health administration. The first section is merely an introduction to the concepts presented. Section II addresses major economic concepts with an emphasis on macroeconomics, while the second section discusses accounting concepts that will help health planners distinguish between accounting and economic terms, as both disciplines often use the same terms but mean slightly different things due to their differing focuses.